2016
DOI: 10.1371/journal.pone.0145912
|View full text |Cite
|
Sign up to set email alerts
|

A New ELISA Using the ANANAS Technology Showing High Sensitivity to diagnose the Bovine Rhinotracheitis from Individual Sera to Pooled Milk

Abstract: Diagnostic tests for veterinary surveillance programs should be efficient, easy to use and, possibly, economical. In this context, classic Enzyme linked ImmunoSorbent Assay (ELISA) remains the most common analytical platform employed for serological analyses. The analysis of pooled samples instead of individual ones is a common procedure that permits to certify, with one single test, entire herds as “disease-free”. However, diagnostic tests for pooled samples need to be particularly sensitive, especially when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…A single NP contains ~ 50 avidins and 1200 biotin-binding sites (BBS) and has ~6000 nm 2 available for surface functionalization. 11 13 They can be functionalized with stoichiometric control by simply mixing with biotinylated functional elements at desired biotin:BBS molar ratios and no purification is necessary if neither the BBS become saturated nor the surface area available is exceeded 11 13 . Provided these two requirements are fulfilled, an infinite number of surface composition combinations can be conveniently generated and screened so that, in principle, selection of the best performing composition is relatively easy to perform.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A single NP contains ~ 50 avidins and 1200 biotin-binding sites (BBS) and has ~6000 nm 2 available for surface functionalization. 11 13 They can be functionalized with stoichiometric control by simply mixing with biotinylated functional elements at desired biotin:BBS molar ratios and no purification is necessary if neither the BBS become saturated nor the surface area available is exceeded 11 13 . Provided these two requirements are fulfilled, an infinite number of surface composition combinations can be conveniently generated and screened so that, in principle, selection of the best performing composition is relatively easy to perform.…”
Section: Resultsmentioning
confidence: 99%
“…In the two biotin-doxorubicin conjugates the drug was linked through an acid-reversible hydrazone bond and the derivatives differ for the length of the spacer between biotin and the drug (no spacer— biotin-Hz-doxo —or a 5 KDa PEG— biotin-PEG-Hz-doxo ). The 5 KDa PEG spacer in both the Atto488 and doxorubicin reagents was selected to maximize the NP PEG surface protection to guarantee long-term colloidal stability 10 , whereas the use of biotin-Hz-doxo permits to maximize drug loading by exploiting all of the available BBS, as steric impediments do not permit to saturate all of the available BBS with the bulky PEG reagent 11 13 . Finally, the 5 KDa spacer in biotin-PEG-cetux was selected to guarantee exposure of the targeting moiety at the NP outer surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies demonstrated the importance of the within-pool prevalence and of the stage of lactation (variable levels of IgG) in the sensitivity of gE conventional assays [ 13 ]. Nevertheless, new strategies can be adopted to increase sensitivity in BM or PM serological investigations [ 14 ] as well as in the surveillance plan strategies [ 15 ]. In a recent study [ 10 ] we described a new approach for IBR surveillance, based on the use of a novel gE indirect ELISA applied to concentrated/purified BM samples.…”
Section: Discussionmentioning
confidence: 99%
“…First, the total number of samples tested was relative low, secondly the report included results for both commercial and in-house ELISA kits (with the former performing better) and finally the indirect kits used in the study have now largely been superseded by a new generation of highly sensitive kits (EFSA, 2006). In regard to gE ELISAs, much higher Se values (99-100%) have been reported (EFSA, 2006) while newer test methodologies, formats and antibody concentration techniques offer the possibility of increased Se values (Bertolotti et al, 2015;Casarin et al, 2016).…”
Section: Environmentmentioning
confidence: 99%